IMPLEMENTATION OF MUROTTAL AL-FATIHAH AGAINST CLIENTS RISK OF VIOLENCE AT THE CLENDER HOSPITAL, EAST JAKARTA - Amrullah (International Journal of Islamic and Complementary Medicine, 2020)
Data from the World Health Organization (WHO) (2009) estimates that 450 million people worldwide experience mental disorders, about 10% of adults experience mental disorders and 25% of the population is estimated to experience mental disorders at a certain age during their life. This age usually occurs in young adults between the ages of 18-21 years. Other data from the National Institute of Mental Health shows that the rate of mental disorders reaches 13% of the disease as a whole and is expected to grow to 25% in 2030. The highest prevalence of mental disorders in Indonesia is in the province of the Special Capital Region (DKI) Jakarta (24, 3%), followed by Nagroe Aceh Darussalam (18.5%), West Sumatra (17.7%), NTB (10.9%), South Sumatra (9.2%), and Central Java (6.8%). while based on data Basic Health Research (2007). It shows that the national prevalence of mental disorders reaches 5.6% of the population, four to five people are suffering from mental illnesses. Based on these data, Indonesia's annual data that experience mental disorders is always increasing (MOH (2008). The increase in the proportion of mental disorders in the data obtained in Riskesdas 2018 is quite significant compared to Riskesdas in 2013, increasing from 1.7% to 7% of Indonesia's population (Riskesdas, 2018). In our country, there are approximately 2,400,000 children with mental disorders.